2008
DOI: 10.1016/j.robot.2007.11.008
|View full text |Cite
|
Sign up to set email alerts
|

What can be done with an embedded stereo-rig in urban environments?

Abstract: International audienceThe development of the Autonomous Guided Vehicles (AGVs) with urban applications are now possible due to the recent solutions (DARPA Grand Challenge) developed to solve the Simultaneous Localization And Mapping (SLAM) problem: perception, path planning and control. For the last decade, the introduction of GPS systems and vision have been allowed the transposition of SLAM methods dedicated to indoor environments to outdoor ones. When the GPS data are unavailable, the current position of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For the heading component, it is noted that the range measurement has more heading information when the surface is close to parallel and farther away from the laser source, with the heading in the body frame with respect to walls (ψ) being the same as the direction to the normal (φ). The geometry of the problem is shown in Figure 13, with the measurement matrix defined in Equation 36.…”
Section: Dilution Of Precisionmentioning
confidence: 99%
“…For the heading component, it is noted that the range measurement has more heading information when the surface is close to parallel and farther away from the laser source, with the heading in the body frame with respect to walls (ψ) being the same as the direction to the normal (φ). The geometry of the problem is shown in Figure 13, with the measurement matrix defined in Equation 36.…”
Section: Dilution Of Precisionmentioning
confidence: 99%
“…Indeed, tracking in urban canyons is a non-trivial problem [2], [1]. It is clear that pose estimation and visual tracking are also important in many applications including robotic vision, augmented reality, medical imaging, etc... Model-based techniques have shown that 3d CAD models are essential for robust, accurate and efficient 3d motion estimation [3], however, they have the major drawback of requiring an a-priori model which is not always available or extremely difficult to obtain as in the case of shapeless objects or large-scale environments.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous localization and mapping (SLAM) benefits from registering wide areas with each stereo pair, the wider the better, as long as the data acquired is consistent enough to be incorporated to the map. The introduction of global navigation satellite systems and vision has led to the adaptation of SLAM methods originally developed for indoors to outdoor environments [5]. The advantage of gathering three-dimensional information cannot be realized at full extent unless the camera can cover the necessary field of view for a given application.…”
Section: Introductionmentioning
confidence: 99%